(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
This study analyzes the fundamental right to housing in Brazil, aiming to discuss the necessary re-signification of its content in the face of the chronic housing deficit and the difficulties of its implementation. The ineffectiveness of consistent public policies, coupled with social inequality and the precariousness of urban planning, gives rise to the need to analyze legal mechanisms capable of realizing this right, mitigating the distance between the constitutional norm and social reality. The adopted methodology consists of bibliographical and documentary research, with a qualitative approach. It is argued that the ineffectiveness of public policies, social inequality, and precarious urban planning require the application of legal mechanisms that transcend mere normative provision, such as land regularization, special urban adverse possession (usucapião), and the right to build on existing slabs (direito de laje), interpreted in light of the social function of property. It is concluded that overcoming the mismatch between the constitutional norm and social reality imposes a change in the bureaucratic culture of legal operators and the government, with joint action between legislation, the State, and civil society being indispensable to build effective housing solutions and prevent the perpetuation of social exclusion, overcoming the "culture of omission."